(untitled) (Jurnal Bahasa Lingua Scientia, 2020)
ABSTRACT This study aims to describe the students’ perception on using E-learning in Academic Writing. 71 students of English Department fourth semester in academic year 2019/2020 had taken a part in this study. Descriptive quantitative survey research was used with closed-ended form questionnaires as the instrument. The result of this research revealed that the use of E-learning in Academic Writing of English Department students of IAIN Kediri was not new for students. Students’ perceptions on using E-learning in Academic Writing was divided into three categories. The categories are student’s behavior on using E-learning in Academic Writing, students’ perceptions about E-learning operational and students’ perceptions about practicing Academic Writing using E-learning. The result showed positive responses from the respondents. Somehow, they disagree that the use of E-learning in Academic Writing could make them more confident, discipline and enjoy learning. It is because of the internet connection and misunderstanding with the teacher’s instruction. It can be said that E-learning restricted students’ interactions with the lecturer and their classmates. The research finding can be used as the evaluation for English language teaching in general.